2004
DOI: 10.1111/j.1442-2018.2003.00167.x
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Health Belief Model: Nurses applying it to young families and their health promotion needs

Abstract: The Health Belief Model (HBM) was reviewed with the aim of modifying it so that it reflected a health promotion stance for young families. Since this model's inception, health professionals like nurses have been involved in using the HBM to guide their practice. It is argued that to assist families, nurses now need a model that is focused on "health." In support of this approach, reorienting the HBM and basing it on "positive" health definitions associated with health promotion, by modifying it through adding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…Consulting was linked to parental perception of illness severity [5], child’s susceptibility to the illness, perceived parental efficacy and ability to cope, their knowledge of the illness and the availability of services. Others have used health belief models to explain the psychological factors influencing help seeking consulting behaviour [10,11], or have modified it to reflect a health promotion stance for young families [28]. This latter approach reoriented the health belief model and based it on positive health definitions associated with health promotion.…”
Section: Discussionmentioning
confidence: 99%
“…Consulting was linked to parental perception of illness severity [5], child’s susceptibility to the illness, perceived parental efficacy and ability to cope, their knowledge of the illness and the availability of services. Others have used health belief models to explain the psychological factors influencing help seeking consulting behaviour [10,11], or have modified it to reflect a health promotion stance for young families [28]. This latter approach reoriented the health belief model and based it on positive health definitions associated with health promotion.…”
Section: Discussionmentioning
confidence: 99%
“…The PHCS has been administered to diverse types of patients[2, 613] as well as generally healthy sub-populations in the United States and other countries[1419]. These studies have confirmed that the PHCS is associated with a number of health outcomes such as better health status, lower depressive symptoms, and better quality of life[9, 2024].…”
Section: Introductionmentioning
confidence: 99%
“…HBM has been widely used and is considered as one of the most useful models in health care prevention and promotion [36]. It offers the ability to understand the different behaviours or attitudes people may develop under the same condition by following or not following certain guidelines or requirements [37].…”
Section: Introductionmentioning
confidence: 99%